2023
DOI: 10.1017/s003329172300243x
|View full text |Cite
|
Sign up to set email alerts
|

Emotion dysregulation in bipolar disorder compared to other mental illnesses: a systematic review and meta-analysis

Michele De Prisco,
Vincenzo Oliva,
Giovanna Fico
et al.

Abstract: People with bipolar disorder (BD) often present emotion dysregulation (ED), a pattern of emotional expression interfering with goal-directed behavior. ED is a transdiagnostic construct, and it is unclear whether it manifests itself similarly in other conditions, such as major depressive disorder (MDD) or borderline personality disorder (BPD), or has specific features in BD. The present systematic review and meta-analysis explored ED and adopted emotion regulation (ER) strategies in BD compared with other psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 99 publications
(106 reference statements)
0
3
0
Order By: Relevance
“…This is the first SR to describe the relationship between ED and BD psychopathology. Together with our two previous SRs, 13,14 it represents a primer in understanding the ED construct in BD, which has previously received little attention. Enhanced knowledge in this area may identify specific treatments that can optimize ED outcomes according to personalized medicine and promote recovery by aiding the development of new transdiagnostic treatments 36 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…This is the first SR to describe the relationship between ED and BD psychopathology. Together with our two previous SRs, 13,14 it represents a primer in understanding the ED construct in BD, which has previously received little attention. Enhanced knowledge in this area may identify specific treatments that can optimize ED outcomes according to personalized medicine and promote recovery by aiding the development of new transdiagnostic treatments 36 .…”
Section: Discussionmentioning
confidence: 89%
“…Existing systematic reviews (SR) and meta‐analyses (MA) showed that patients diagnosed bipolar disorder (BD) are particularly prone to higher ED levels 13,14 . BD is a severe chronic mental illness characterized by changes in synaptic plasticity and neuronal connectivity resulting from several genetic, epigenetic, and environmental factors 15–17 .…”
Section: Introductionmentioning
confidence: 99%
“…Affective disorders are one of the leading causes of morbidity and mortality after cardiovascular diseases, cancer, and road traffic accidents. Bipolar disorder (BD) belongs to affective disorders and is characterized by emotional dysregulation [ 8 , 9 , 10 ], affecting roughly >1% of the global population, regardless of sex, ethnicity, or social income [ 11 , 12 , 13 , 14 ]. It is associated with significant psychosocial morbidity and mortality due to increased suicidality and medical poly-comorbidity [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%